Designing an AI Healthcare System: EHR and Priority-Based Medical Segmentation Approach - Akhtar, Zarif Bin (Universitas Muhammadiyah Yogyakarta, Indonesia, 2023)
Since the formulation of digital systems and the rapid advancements in the domain of modern technology in terms of computing and device peripherals that resides within the realm of which is revolving around perspective concepts, with its associated aspect of implementations such as Artificial Intelligence (AI), Machine Learning, Deep Learning, Cloud Computing, Smart Digital Systems are now booming out with an acceleration of apex proportion in the various diversity of fields within the domain of engineering. Especially in the field of Bio-Medical Engineering these aspects can play significant roles considering for the human conditions and anatomy perspective. Health which is the top priority of perspective, giving scope to human conditions and with the continuation of time and increase of diseases along with, fatal issues revolved around the human health, it is of upmost and great importance to find the optimum solutions for all the cases of scenarios. This research focuses on that aspect of perspective towards the Electronic Health Record (EHR) system with its usage in accordance with an Artificial Intelligence (AI) for providing an optimal solution presented to it where the issues are tackled with prioritization and segment queue and an overall proficiency for the optimum results in direct relation to performance efficiency with the prototype version that is developed, deployed and experimented with for the conduction of this research.